Using visualization for visualization : an ecological interface design approach to inputting data - Wright, H.; Mathers, C.; Walton, J. P. R. B. (Computers & graphics, 2013)
Visualization is experiencing growing use by a diverse community, with continuing improvements in the availability and usability of systems. In spite of these developments the problem of how first to get the data in has received scant attention: the established approach of pre-defined readers and programming aids has changed little in the last two decades. This paper proposes a novel way of inputting data for scientific visualization that employs rapid interaction and visual feedback in order to understand how the data is stored. The approach draws on ideas from the discipline of ecological interface design to extract and control important parameters describing the data, at the same time harnessing our innate human ability to recognize patterns. Crucially, the emphasis is on file format discovery rather than file format description, so the method can therefore still work when nothing is known initially of how the file was originally written, as is often the case with legacy binary data. © 2013 Elsevier Ltd.
Keywords: File organisation; Information search; Ecological interface design; Pattern recognition; Scientific visualization